Sodium transport and attenuation in soil cover materials for oil sands mine reclamation. (January 2019) - Vessey, Colton J.; Lindsay, Matthew B.J.; Barbour, S. Lee
Abstract: Reclamation soil covers are used in oil sands mine closure to support vegetative growth over tailings. Geochemical processes within these covers may impact solute transport during upward migration of oil sands process-affected water (OSPW) from the underlying tailings. In this study, we examined the geochemical processes controlling Na transport and attenuation within the peat and clay-till cover soils at Sandhill Fen in northern Alberta, Canada. We analyzed soil core samples collected along transects of this 54-ha pilot-scale oil sands mine reclamation wetland. The geochemical (Na, Ca, Mg, K, Cl, SO4, HCO3 ) and isotopic (δ 2 H, δ 18 O) compositions of extracted pore water were analyzed statistically to identify OSPW and fresh surface water within the cover. Depth-dependent trends in pore water sodium concentrations were not apparent, suggesting that the soil cover had been fully flushed by a mixture of OSPW and fresh surface water used to flood the fen. Relative concentrations of Na, Ca and Mg were used to define the extent of cation exchange within the clay cover. Complementary laboratory column experiments showed that cation exchange removed up to 50% of dissolved Na as the first pore volume of simulated OSPW passed through the peat and till. However, Na attenuation by these materials declined rapidly and was limited after 4 (peat) to 7 (till) pore volumes of OSPW flushing. Reactive transport modeling confirmed that cation exchange was the dominant control on Na attenuation and corresponding Ca and Mg release within the till and peat columns. Mineral precipitation-dissolution reactions also influenced dissolved Ca and Mg concentrations and, therefore, indirectly impacted Na attenuation. Overall, this study helps constrain the geochemical processes controlling Na transport and attenuation in oil sands reclamation soil covers exposed to OSPW, and indicates that the attenuation of Na from OSPW by these covers is short-lived. Highlights: We examined sodium attenuation by soil covers used in oil sands mine reclamation. Field, laboratory and modeling studies examined attenuation processes and capacity. Ion exchange reactions are dominant sodium attenuation process. Mineral dissolution reactions indirectly influence sodium attenuation. Reclamation soil covers provide limited, short-term sodium attenuation capacity.